2023
DOI: 10.20944/preprints202309.1385.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Rationale for Dietary Lutein Supplementation in Post COVID-19 and mRNA Vaccine Injury Syndromes

Anthony M Kyriakopoulos,
Greg Nigh,
Peter A McCullough
et al.

Abstract: Lutein, a plant-derived xanthophyl-carotenoid, is an exceptional antioxidant and anti-inflammatory constituent found in food. Elevated concentrations of lutein found in human blood and plasma, due to high dietary intake, are beneficial against eye disease and improve cardiometabolic health. Lutein plays an important protective role against the development of neurological disorders, including Alzheimer’s disease (AD), multiple sclerosis (MS) and Parkinson’s disease (PD). It has also been sho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 127 publications
0
1
0
Order By: Relevance
“…Researchers have reported that the SARS-CoV-2 mRNA-LNP vaccine may pose the risk of development and progression of cancer [25][26][27][28]. In addition, several case reports have described cancer developing or worsening after vaccination and discussed possible causal links between cancer and mRNA-LNP vaccination [29][30][31][32][33][34].…”
Section: Influence Of Multiple Mrna-lnp Vaccine Dosesmentioning
confidence: 99%
“…Researchers have reported that the SARS-CoV-2 mRNA-LNP vaccine may pose the risk of development and progression of cancer [25][26][27][28]. In addition, several case reports have described cancer developing or worsening after vaccination and discussed possible causal links between cancer and mRNA-LNP vaccination [29][30][31][32][33][34].…”
Section: Influence Of Multiple Mrna-lnp Vaccine Dosesmentioning
confidence: 99%